Nurturing Nature: A History of Botanical Gardens in Indonesia - Amini, Mutiah; Darini, Ririn; Setyowati, Eny (Balai Pelestarian Kebudayaan Wilayah X, 2023)
This article discusses various efforts to create a healthy landscape for the sake of environmental balance. The colonial government-initiated nature preservation with tropical plant studies starting in 1817. Initiated by a government policy reform in 1816, this led to the establishment of the Bogor Botanical Garden on May 18, 1817, the Cibodas Botanical Garden on April 11, 1852, the Purwodadi Botanical Garden on January 30, 1941, and finally, the Eka Karya Botanical Garden on July 15, 1959. Over time, botanical gardens evolved into centers for plant research and conservation with increasingly widespread utilization. Through historical research utilizing contemporary sources, three important conclusions are drawn. First, caring for and creating a healthy landscape reflects an early awareness of environmental conservation in Indonesia that began in 1816. Second, by endeavoring to maintain and create a healthy landscape, the government played a role as an institution in establishing long-term ecosystem balance. Third, through the development of a healthy landscape, various national interests are more easily realized, particularly in supporting the nation’s economic development.